Implementasi Algoritma Turbo Boyer Moore untuk Pencarian Data pada Transaksi Keuangan Duta Phonecell Sawah Lebar - Gunawan, Gunawan; Kirman, Kirman (Jurnal Media Infotama, 2019)
Small and Medium Enterprises or often abbreviated to SMEs which are one of the important parts of the economy of a country or region, Duta phonecell Sawah Besar is one of the credit suppliers or traders. In the current system, transaction recording still uses books. a place to store summaries of data from data sources and collects data from various sources in order to obtain a better view of a business process. One of the string matching algorithms used is the Boyer Moore algorithm. Where the Boyer Moore string matching algorithm for a file is to be executed, the file is not immediately permitted to be executed. The research was carried out at Duta phonecell which is located at Sawah lebar, Bengkulu City. Moore's turbo boyer algorithm cannot be used in the search process because it is not proven to be used on objects. This is because the field page is too small and has not searched for tests in a long sequence of tests. The application was successfully created but did not apply the Turbo Boyer Moore algorithm. The suggestion for this research is to try to continue the application of the Turbo Boyer Moore algorithm in the search process in a long and large test. Also included is the Turbo Boyer Moore algorithm only for searching for certain tests that are different throughout the long test data